A Research on Gold Loan Industry in Non-Banking Financial Companies (NBFCs): Exploring the Landscape of Gold Loan Industry in Non-Banking Financial Companies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Non-bank financial firms, or NBFCs, are investment banks that provide banking services, but have no banking license. This study focuses primarily on the work regulations of NBFC in India, its importance, the sources of NBFC funding and its future prospects. In structure, function, production, activity of the regulatory framework, functional field besides the relation between the financial system and the financial system, economic development. Many of the studies have already been performed and published in India to study the activities and functioning of NBFCs and NBFC assessments. The organizational profile, the growth forecast, market volume statistics over the years and also the financial performance of the NBFCs in India to provide important peripheral background for the study are also provided comprehensive consideration. An analysis was also provided of recent developments in the financial sector structure and its impact on non-bank financial institutions.